PENINGKATAN KEMAMPUAN MENYIMAK MELALUI MEDIA FOLKLOR “PETUALANGAN KE AIR TERJUN DEDARI” PADA SISWA KELAS IV SD BALI BILINGUAL SCHOOL - Wahyu Nurhidayati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to improve the listening skills of fourth-grade students at SD Bali Bilingual School in Indonesian language subjects through the application of local folklore media entitled "Petualangan ke Air Terjun Dedari". The primary problem underlying this research was the students' low listening comprehension and concentration during the learning process, which affected their learning outcomes. This study was a Classroom Action Research (CAR) conducted in two cycles. Each cycle consisted of planning, action, observation, and reflection stages. The subjects of this research were 22 fourth-grade students at SD Bali Bilingual School. Data collection techniques included listening comprehension tests and student activity observation sheets. The results demonstrated a significant improvement in students' listening skills. In the pre-cycle phase, the classical learning completeness was only 31.8% (7 students). Following the implementation of actions in Cycle I using printed folklore media and guided storytelling, the classical completeness increased to 54.5% (12 students). In Cycle II, following the optimization of morning time management and the implementation of a U-shaped seating arrangement to enhance student focus, the classical completeness rose sharply to 86.36% (19 students). Based on these findings, it can be concluded that the use of the local folklore media "Petualangan ke Air Terjun Dedari" is effective in improving the listening skills and learning concentration of elementary school students.